Regency Christmas liaisons - Merrill, Christine; James, Sophia (Sophia Annie); Kaye, Marguerite (Harlequin historicals., 2021)
A trio of Christmas stories set in Regency England, with poor relations, widows, brooding noblemen and dashing strangers all get their happily ever afters - or do they?